Neuroscientific insights and therapeutic approaches to eating disorders - Kukreja, Jyoti; M., Geetha; Poonia, Ramesh Chandra; Tewari, Veena; Verma, Rahul R. (IGI Global, 2024)
In the complex landscape of binge eating disorders, a pervasive and intricate challenge unfolds. Binge eating, characterized by Binge eating disorders, is a difficult challenge that requires a nuanced understanding of the underlying neuroscientific mechanisms for effective prevention and intervention strategies. There is a pressing need to bridge the gap between cutting-edge neuroscientific research and the evolving therapeutic landscape. To address this, our groundbreaking book is tailored for academic scholars in the neuroscientific community. We offer a transformative journey into the heart of binge eating disorders, unraveling the mysteries that govern neural circuits, genetic factors, hormonal imbalances, and more.Neuroscientific Insights and Therapeutic Approaches to Eating Disorders is a beacon for researchers, clinicians, and mental health professionals seeking to deepen their comprehension of eating disorders. It addresses the present-day challenges posed by binge eating and presents a roadmap for future research and clinical applications. This comprehensive resource synthesizes the latest findings in neuroscience with innovative therapeutic approaches, ultimately paving the way for improved outcomes. Episodes of excessive food consumption and loss of control demand a nuanced understanding of the underlying neuroscientific mechanisms for effective prevention and intervention strategies. Our present reality is marked by a pressing need to bridge the gap between cutting-edge neuroscientific research and the evolving therapeutic landscape. The intricate relationship between the brain and eating disorders calls for a comprehensive resource that not only dissects the neurobiological foundations but also illuminates the path toward innovative therapeutic approaches.